Berberine Intervention Mitigates Myocardial Ischemia-Reperfusion Injury in a Rat Model: Mechanistic Insights via miR-184 Signaling - Yang H; Cao G; Li X; Zhao Z; Wang Y; Xu F (Biologics: Targets & Therapy)
Haichen Yang,1,* Gang Cao,2,* Xia Li,3 Zhikun Zhao,4 Yong Wang,5 Fei Xu6 1Department of Emergency, The Affiliated Huai’an Hospital of Xuzhou Medical University and Huai’an second People’s Hospital, Huai’an, People’s Republic of China; 2Department of Respiratory Medicine, Hongze District People’s Hospital, Hongze, Jiangsu, People’s Republic of China; 3Department of Geriatric, The Affiliated Huai’an Hospital of Xuzhou Medical University and Huai’an Second People’s Hospital, Huai’an, People’s Republic of China; 4Department of Intensive Care Unit, The Affiliated Huai’an Hospital of Xuzhou Medical University and Huai’an Second People’s Hospital, Huai’an, People’s Republic of China; 5Department of Cardiology, The Affiliated Huai’an Hospital of Xuzhou Medical University and Huai’an Second People’s Hospital, Huai’an, People’s Republic of China; 6Department of Intensive Care Unit, Lianshui County People’s Hospital, Huai’an, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yong Wang, Department of Cardiology, The Affiliated Huai’an Hospital of Xuzhou Medical University and Huai’an Second People’s Hospital, Huai’an, People’s Republic of China, Email pangpang1180@163.com Fei Xu, Department of Intensive Care Unit, Lianshui County People’s Hospital, Huai’an, People’s Republic of China, Email xufei_21769@163.comBackground: Ischemia-reperfusion (I/R) injury is a major contributor to myocardial dysfunction and tissue damage. A natural alkaloid-Berberine having a wide range of pharmacological properties, has garnered interest for its potential cardioprotective properties. This study aimed to investigate the protective effects of berberine on myocardial tissue in a rat model of myocardial ischemia-reperfusion (I/R) injury. Additionally, the study explored the role of the miR-184/NOTCH1 signaling pathway in mediating these effects.Methods: Male Wistar rats were randomly assigned to five groups: sham-operated control, I/R injury, I/R treated with berberine, I/R treated with inhibitor NC and I/R treated with a miR-184 inhibitor. The I/R injury was induced by ligating the left anterior descending (LAD) coronary artery for 30 minutes, followed by 2 hours of reperfusion. Berberine was administered orally at 100 mg/kg/day for 2 weeks, and the miR-184 inhibitor was administered via intraperitoneal injection. Hemodynamic parameters were recorded using a pressure sensor connected to a catheter inserted into the left ventricle. Myocardial infarct size was assessed using TTC staining, while histological and molecular changes were evaluated through H&E staining, TUNEL assay, and Western blotting. The expression levels of target genes were analyzed using quantitative real-time PCR (qRT-PCR).Results: Berberine significantly reduced myocardial infarct size and improved hemodynamic parameters compared to the untreated I/R group. Additionally, berberine treatment attenuated apoptosis as evidenced by decreased TUNEL-positive cells. The miR-184 inhibitor also demonstrated protective effects by modulating key signaling pathways involved in myocardial injury. Western blot analysis revealed downregulation of NOTCH1 and HES1 expression in treated groups, indicating a potential mechanism for the observed cardio protection.Conclusion: Berberine and miR-184 inhibition offer significant protection against myocardial ischemia-reperfusion injury. These findings suggest that targeting miR-184 and associated pathways may be a promising therapeutic strategy for reducing cardiac damage following ischemia-reperfusion.Keywords: berberine, myocardial ischemia-reperfusion, cardioprotective effects, miR-184, NOTCH1 signaling pathway